Photocatalytic Applications of Fe–Ag Co-Doped TiO2 Nanoparticles in Removal of Flumioxazin Pesticide Residues in Water - Nageswara Rao, Tentu; Prashanthi, Y.; Ahmed, Faheem; Kumar, Shalendra; Arshi, Nishat; Rajasekhar Reddy, G.; Manohra Naidu, Tentu (Frontiers in Nanotechnology, 2021)
Fe–Ag co-doped TiO2 nanoparticles (NPs) were prepared as a photocatalyst using a precipitation method for the removal of flumioxazin pesticide residues in water. The analytical method was validated with specificity, linearity, recovery, precision, the limit of quantification, and detection limit. Linearity was determined by different known concentrations of standard solutions. Detection limit was identified as the lowest concentration resulting in a 3-fold response to baseline noise. Photolytic and photocatalytic studies were conducted in borosil glass bottles under sunlight at a single fortification level (1.0 μg/mL) in Milli-Q water with various pH values (pH 4.0, 7.0, and 9.0). The optimum catalyst concentration recommended for complete degradation was found to be 50 mg/L under sunlight. The HPLC-UV method was used to determine flumioxazin residues in water, and the rate constant, DT50, and DT90 values were calculated from the data obtained. The photolytic results do not indicate a significant residue loss due to adsorption. Fe–Ag co-doped TiO2 NPs are an outstanding decontaminating catalyst in various water samples.